Synthesis and proton-conductive behaviour of two MOFs with covalently bonded imidazoles in the channels - Chen, Kun-Peng; Ma, Yue; Ren, Hong-Xia; Zhang, Chen-Xi; Wang, Qing-Lun (Dalton transactions : an international journal of inorganic chemistry, 2024)
Immobilization of imidazole molecules as proton carriers into MOFs to facilitate proton conduction is a general strategy for developing high proton conductive materials. Herein, we designed two imidazole substituted phthalic acid ligands and constructed two novel MOFs, {[Zr 6 (OH) 16 (H 3 L 1 ) 4 ]Cl 8 ·20H 2 O} n [ Zr-MOF ; H 3 L 1 = 2-(1 H -imidazol-4-yl) methylaminoterephthalic acid] and {Gd(HCOO)(H 2 L 2 ) 2 } n [ Gd-MOF ; H 3 L 2 = 5-(1 H -imidazol-4-yl)methylaminoisophthalic acid] and fully studied their porous nature, stability and water-assisted proton conduction. The resulting Zr-MOF exhibits a high proton conductivity of 1.82 × 10 −2 S cm −1 at 98% RH and 80 °C, while Gd-MOF has a proton conductivity of 3.01 × 10 −3 S cm −1 at 98% RH and 60 °C. Based on two imidazole substituted phthalic acid ligands, two new metal-organic frameworks have been synthesized. Both complexes exhibit impressive proton conductivities under 98% RH.